High speed CMOS multiplier design - Tay, Wen Kai (Nanyang Technological University, 2022)
Due to increasing popularity of real-time systems, there is an increasing need for high-speed circuits to process data and deliver an output for subsequent circuits to be used. A multiplier is a type of circuit crucial in processing data and generally the slowest in the system. To implement a high-speed CMOS multiplier, we would have to consider its circuit design which comprises of its logic gates. By using different types of logic combinations, we can achieve the function of a multiplier. The speed of the multiplier would be affected by the delay of the logic circuit. This would be achieved by using Verilog to design the circuit and Synopsys to synthesize the circuit. The different designs will be analysed, and the delay of the output compared. The proposed multiplier design is about 2 times faster than the array multiplier. The simulations are performed using AMS 0.35um technology.